2020
DOI: 10.1055/s-0040-1718726
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Profile of Gangliosidosis from Southern Part of India

Abstract: Gangliosidoses are progressive neurodegenerative disorders caused by the deficiency of enzymes involved in the breakdown of glycosphingolipids. There are not much data about gangliosidosis in India; hence, this study was planned. The aim is to study the clinical, biochemical, and molecular profile of gangliosidosis. A retrospective chart review, in the pediatric neurology department from January 2015 to March 2020, was performed. Children diagnosed with Gangliosidosis were included. The disorder was confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Interestingly, the authors observed that the number of hyperpigmented macules increased with the progression of the disease, although no genotype-phenotype correlation or association with the overall disease severity was evident [21]. Similar results were seen in other Indian and Chinese cohorts [22,23], thus supporting the association of extensive congenital DM with GM1 gangliosidosis in Asian and darker skin phototypes patients from India.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, the authors observed that the number of hyperpigmented macules increased with the progression of the disease, although no genotype-phenotype correlation or association with the overall disease severity was evident [21]. Similar results were seen in other Indian and Chinese cohorts [22,23], thus supporting the association of extensive congenital DM with GM1 gangliosidosis in Asian and darker skin phototypes patients from India.…”
Section: Discussionmentioning
confidence: 56%
“…Depending on this aspect, it would be advisable to assess caregiver fatigue, as it can be an important and influential factor in the development and evolution of the patient’s illness [ 17 , 50 , 51 ]. Considering the role of the caregiver and their relationship with the patient diagnosed with Tay–Sachs disease was a nuance mentioned by the group of experts since, in a situation of total or partial dependency, the state of the main caregiver can have a direct impact on the patient [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] The normal enzyme is also reported in other LSDs like in MLD due to Saposin B or Arylsulfatase A deficiency,[ 7 ] and the AB variant of gangliosidosis. [ 9 ]…”
mentioning
confidence: 99%